2021
DOI: 10.3390/nu13020561
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaw (MRONJ): Are Antiresorptive Drugs the Main Culprits or Only Accomplices? The Triggering Role of Vitamin D Deficiency

Abstract: Osteonecrosis of the jaw (ONJ) is a severe clinical condition characterized mostly but not exclusively by an area of exposed bone in the mandible and/or maxilla that typically does not heal over a period of 6–8 weeks. The diagnosis is first of all clinical, but an imaging feedback such as Magnetic Resonance is essential to confirm clinical suspicions. In the last few decades, medication-related osteonecrosis of the jaw (MRONJ) has been widely discussed. From the first case reported in 2003, many case series an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 87 publications
(96 reference statements)
0
11
0
2
Order By: Relevance
“…There is weak evidence for a role of vitamin D deficiency in MRONJ development. Studies have shown associations with chronic periodontitis or caries risk ( 47 ). Low vitamin D levels have been associated with ONJ in some ( 48 , 49 ) but not all studies ( 50 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…There is weak evidence for a role of vitamin D deficiency in MRONJ development. Studies have shown associations with chronic periodontitis or caries risk ( 47 ). Low vitamin D levels have been associated with ONJ in some ( 48 , 49 ) but not all studies ( 50 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Desde o primeiro relato, em 2003, sobre as lesões de osteonecrose dos maxilares como efeito advindo do uso constante dos bisfosfonatos, muitos estudos foram realizados no intuito de validar as informações apresentadas por Marx e criar uma base de dados na literatura científica. Quase todos os artigos publicados, desde então, concluem que os fármacos da família bisfosfonatos podem induzir essa condição clínica em seus usuários (CARBONARE et al, 2021). Nesse sentido, em 2013, a AAOMS propôs um sistema de estadiamento com o objetivo de orientar o tratamento de pacientes que foram expostos a terapias com bisfosfonatos, Tabela Tabela 3 -Estratégias de tratamento para a ONJ associada aos bisfosfonatos.…”
Section: Discussionunclassified
“…Em 2014, por causa do aumento de casos de osteonecrose associada a outras terapias com antirresorptivascas/antiangiogênicas e não apenas aos bisfosfonatos, a AAOMS propôs a mudança de nomenclatura da BRONJ para osteonecrose dos maxilares associados a medicamentos (do inglês "medication-related osteonecrosis of the jaw", MRONJ) (CARBONARE et al, 2021). A ONJ é uma patologia de instalação rápida e compromete significantemente a qualidade de vida do indivíduo, clinicamente se apresenta como uma perda da mucosa bucal, expondo o osso subjacente (LACERDA et al, 2017;VILELA-CARVAL et al, 2018).…”
Section: Discussionunclassified
“…Initially, only bisphosphonaterelated osteonecrosis of the jaw (BRONJ) was described in the literature. However, in 2014, the American Association of Oral and Maxillofacial Surgeons recommended the change in the nomenclature of BRONJ to MRONJ, as it was found that other antiresorptives, such as denosumab, and antiangiogenic medications cause similar complications [80][81][82]. The pathophysiology of MRONJ is not completely understood, so its prevention and management remain challenging today.…”
Section: Medication-related Osteonecrosis Of the Jawmentioning
confidence: 99%
“…The pathophysiology of MRONJ is not completely understood, so its prevention and management remain challenging today. Some of the risk factors strongly associated with MRONJ for patients undergoing antiresorptive therapy are infection and mechanical trauma after tooth extraction; moreover, some researchers have observed that a low vitamin D level also may be a risk factor for the development of MRONJ [80,83].…”
Section: Medication-related Osteonecrosis Of the Jawmentioning
confidence: 99%